Wireless network planning of typical SG-IoT - Yue MA; Bingsong LI; Quangui HU (Dianxin kexue)
A SG-IoT wireless network planning method was proposed,the characteristics and differences of multiple wireless technology systems were analyzed in terms of coverage,capacity,networking mode,etc.,and its adaptability to different SG-IoT applications was demonstrated.A basis for the SG-IoT and comprehensively support the construction of the SG-IoT was provided.